2008
DOI: 10.1016/j.physletb.2008.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Review of Particle Physics

Abstract: This biennial Review summarizes much of particle physics. Using data from previous editions, plus 2778 new measurements from 645 papers, we list, evaluate, and average measured properties of gauge bosons, leptons, quarks, mesons, and baryons. We also summarize searches for hypothetical particles such as Higgs bosons, heavy neutrinos, and supersymmetric particles. All the particle properties and search limits are listed in Summary Tables. We also give numerous tables, figures, formulae, and reviews of topics suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

391
5,095
32
11

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 4,761 publications
(5,534 citation statements)
references
References 0 publications
391
5,095
32
11
Order By: Relevance
“…In fact, substituting the present experimental values of the charged lepton masses [2], the formula is valid within the present experimental accuracies. The relative experimental error of the left-hand side (l.h.s. )…”
Section: Jhep05(2009)075supporting
confidence: 68%
See 3 more Smart Citations
“…In fact, substituting the present experimental values of the charged lepton masses [2], the formula is valid within the present experimental accuracies. The relative experimental error of the left-hand side (l.h.s. )…”
Section: Jhep05(2009)075supporting
confidence: 68%
“…Comparing to the present experimental bound Br(K L → eµ) < 4.7 × 10 −12 [2], we obtain a limit v 2 5 × 10 2 TeV. Naively this limit may already be marginally in conflict with the estimated unification scale in the above scenario.…”
Section: Jhep05(2009)075supporting
confidence: 55%
See 2 more Smart Citations
“…with the help of equations (8) and (9). As in the framework of the standard solar model, we assumed that the number of 57 Fe nuclei per unit mass in the Sun is uniform, i.e., that N is independent of r. Using the standard solar model data for the temperature and mass density distributions in the Sun as functions of the radius r [44], we evaluated the integral in the above expression and found that…”
Section: Axion Emission From 57 Fe Nuclei In the Sunmentioning
confidence: 99%